Antioxidant insights: investigating the protective role of oxidative balance in inflammatory bowel disease - Li, Fan; Chang, Yu; Wang, Zhaodi; Wang, Zhi; Zhao, Qi; Han, Xiaoping; Xu, Zifeng; Yu, Chanjiao; Liu, Yue; Chang, Shiyu; Li, Hongyan; Hu, Sileng; et al. (Frontiers in Endocrinology, 2024)
Background Limited studies have investigated the relationship between systemic oxidative stress and inflammatory bowel disease (IBD). The purpose of this study was to explore the relationship between oxidative balance score (OBS) and IBD. Methods We included 175,808 participants from the UK Biobank database from 2006 to 2010. OBS scores were calculated based on 22 lifestyle and dietary factors. Multiple variable Cox proportional regression models, as well as gender stratification and subgroup analysis, were utilized to investigate the relationship between OBS and IBD. Results There is a significant negative correlation between OBS and the occurrence of IBD, ulcerative colitis (UC), and Crohn’s disease (CD). Additionally, OBS is significantly negatively correlated with intestinal obstruction in CD patients. Gender stratified analysis suggest a significant correlation between OBS and CD in female patients, particularly pronounced in those under 60 years old. Sensitivity analysis indicates a significant negative correlation between lifestyle-related OBS and diet-related OBS with the occurrence of CD in females, diet-related OBS is negatively correlated with CD in males. Conclusion OBS showed a significant negative correlation with IBD, especially in female CD patients. This study underscores the importance of antioxidant diet and lifestyle, which may provide a greater advantage for female CD patients.